APPLICATION OF NITRITES AND NITRATES AS PRESERVATIVES IN PROCESSED MEAT PRODUCTION - Silovksa NIkolova Aleksandra; Belichovska Daniela (Knowledge International Journal, 2020)
Shelf life increasing and safety of meat products, as well as food in general, marks the mankind development through history. At the beginning, the preserving methods have been developed on experience only, but later the development have been based on scientific facts. Nowadays, modern food production is hard to be imagined without preservatives, among which the most commonly present in meat industry are nitrites: potassium nitrite (E 249) and sodium nitrite (E 250) and nitrates: sodium nitrate (E 251) and potassium nitrate (E 252). These preservatives are used in thermally processed and thermally unprocessed meat products. Their use limits and prevents the growth and multiplication of microorganisms, thus inhibiting the growth and multiplication of pathogen bacteria Clostridium botulinum. The nitrite ion (-NO2) has got bacteriastatic and bactericidal action. Without their use it is very difficult to get microbiologically safe product. They, also, influence the product`s shelf life extension. Nitrates, unlike nitrites, have no significant influence on the growth and multiplication of microorganisms. They need to be reduced to nitrites by of the action of denitrifying bacteria. Nitrites are used in meat industry for development and stability of pink-redish colour in meat products, as well as for preventing lipid oxidation and improving taste and odour in meat product. By adding nitrites and nitrates during meat processing, there is a reaction of nitrite with amines, in which case cancer causing and toxic N-nitrosamines appears. Due to these reasons their use and dosage has been limited by a law legislative. But, it is important to emphasize that the usage of nitrites and nitrates needs to be within the framework of the legislatives which regulates their use. If they are used excessively, they can be a serious threat for human health
Keywords: preservatives, nitrites, nitrates, meat processed products, application